Breaking the chains of traditional finance: A taxonomy of decentralized finance business models - Max Beinke; Jan Heinrich Beinke; Eduard Anton; Frank Teuteberg (Electronic Markets, 2024)
Recently, the looming bankruptcy of Credit Suisse, which ultimately led to its merger with UBS, has intensified the discussion surrounding the need for more transparent and democratic financial markets. Decentralized finance (DeFi) represents a departure from traditional financial intermediation by leveraging blockchain technology and smart contracts. Despite its growing importance, limited research has been conducted on the business models of DeFi services. This study aims to address this gap by examining the business models of various DeFi services, identifying key drivers of innovation, differentiation, and value creation. Using a rigorous taxonomy development framework, we identify 12 dimensions and 47 characteristics that operationalize business models in DeFi. Our findings contribute to a better understanding of the transformation of financial services through blockchain technology and provide valuable insights for DeFi entrepreneurs, investors, and policymakers.
Keywords: G15; G23; O32; O33; 620; Decentralized finance; Blockchain; Business model; Taxonomy; Web3